SEX TABOOS AS REGULATORY MEASURE AGAINST SEXUAL IMMORALITY AMONG THE IGBO PEOPLE OF ANAMBRA STATE. (2012)
Notable research works have been conducted on sexuality and taboos in Igbo land. However not much work has been done on how sex taboos and their breach have become a norm or cultural model for the regulation and prevention of all forms of bad sexual behaviours and sexually transmitted diseases. This research, therefore, explored sex taboos in Igboland and the consequences of breaching them, with a view to determining how these sex taboos serve as a means of controlling sexual immorality among the Igbo people of Anambra State. Mitchell’s theory of cultural communities was employed in order to identify the features of cultural indices, shared values and language/religious affinities etc. Anambra State served as the study area. This state is divided into four geo-political zones, each of which has, at least, four local government areas. At least two local government areas were chosen from each zone in order to gather credible information. Data were collected using Focus Group Discussion, oral interviews, key informants ,and non-participant observation techniques. The data were subjected to content analysis. Sex taboos are still in existence in the study area and still carry the same consequences as of old, despite the influence of modern religions, such as Christianity. According to the respondents, the breach of sex taboos brings, pressure, denial of privileges, illness and death. The custodians of the cleansing processes are still consulted by those who have breached the taboos and they charge different amounts, depending on the gravity and nature of the offence. The objects for the cleansing of culprits include kola nuts (at least two but preferably four or multiple of it) Nzu (white clay chalk), sacred “Ofo”, wine, a giant hen, goat, young chick, alligator pepper (ose oji), a piece of white cloth a big stone, yam with other condiments for cooking and a life branch of any of these Igbo sacred trees; Abosi or Echichi. To some extent, the consequences of breach of the taboos on the culprit and his or her family have served as deterrents to people. This has helped in maintaining some sexual sanity in the community, especially among those Igbo who are resident at home. Sex taboos are an integral part of the life of the people of Anambra State in particular and the Igbo people in general. They are a means of ensuring that the relationship of man with the spirit world is intact. In view of the effects of the breach of sexual taboos on the people of Anambra State, further research could be conducted on how these sex taboos are perceived in the entire Igbo land.